DI PASAR TOROBULU KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Hikmah, Al; Baheri, Baheri; Nusantara, Ambo Wonua (Universitas Halu Oleo, 2023)
This study aims to determine the practice of buying and selling rice in terms of Islamic economic aspects in the Torobulu market, Laeya District, South Konawe Regency. The type of data used in this research is descriptive qualitative data. Methods of data collection by direct observation, questionnaires, and documentation. The data analysis method used is where the data obtained are analyzed and presented in the form of tables and then given explanations and conclusions. Based on the results of the study, it was stated that the practice of buying and selling rice in terms of the Islamic economic aspect in the Torobulu market, Laeya District, South Konawe Regency had not been implemented very well where in 8 (eight) indicators including the sale and purchase price transactions of 80% carried out according to Islamic law, 100% contract is carried out according to Islamic law, 100% bargaining is not carried out according to Islamic law, 100% price agreement is carried out according to Islamic law, 70% free of tadlis is carried out according to Islamic law, 30% free of gharar according to Islamic law, 100% hospitality according to Islamic law, mutual pleasure of 100% doing according to Islamic law.